Lipid metabolism and functional assessment of discarded human livers with steatosis undergoing 24 hours of normothermic machine perfusion. Issue 2 (29th January 2018) - Liu, Qiang; Nassar, Ahmed; Buccini, Laura; Iuppa, Giuseppe; Soliman, Basem; Pezzati, Daniele; Hassan, Ahmed; Blum, Matthew; Baldwin, William; Bennett, Ana; Chavin, Kenneth; Okamoto, Toshihiro; et al.
Abstract : Normothermic machine perfusion (NMP) is an emerging technology to preserve liver allografts more effectively than cold storage (CS). However, little is known about the effect of NMP on steatosis and the markers indicative of hepatic quality during NMP. To address these points, we perfused 10 discarded human livers with oxygenated NMP for 24 hours after 4‐6 hours of CS. All livers had a variable degree of steatosis at baseline. The perfusate consisted of packed red blood cells and fresh frozen plasma. Perfusate analysis showed an increase in triglyceride levels from the 1st hour (median, 127 mg/dL; interquartile range [IQR], 95‐149 mg/dL) to 24th hour of perfusion (median, 203 mg/dL; IQR, 171‐304 mg/dL; P = 0.004), but tissue steatosis did not decrease. Five livers produced a significant amount of bile (≥5 mL/hour) consistently throughout 24 hours of NMP. Lactate in the perfusate cleared to <3 mmol/L in most livers within 4‐8 hours of NMP, which was independent of bile production rate. This is the first study to characterize the lipid profile and functional assessment of discarded human livers at 24 hours of NMP. Liver Transplantation 24 233–245 2018 AASLD.